Low and High Molecular Mass Dithienopyrrole–Naphthalene Bisimide Donor–Acceptor Compounds: Synthesis, Electrochemical and Spectroelectrochemical Behaviour. Issue 12 (30th January 2017) - Rybakiewicz, Renata; Glowacki, Eric D.; Skorka, Lukasz; Pluczyk, Sandra; Zassowski, Pawel; Apaydin, Dogukan Hazar; Lapkowski, Mieczyslaw; Zagorska, Malgorzata; Pron, Adam
Abstract: Two low molecular weight electroactive donor–acceptor–donor (DAD)‐type molecules are reported, namely naphthalene bisimide (NBI) symmetrically core‐functionalized with dithienopyrrole (NBI‐(DTP)2 ) and an asymmetric core‐functionalized naphthalene bisimide with dithienopyrrole (DTP) substituent on one side and 2‐ethylhexylamine on the other side (NBI‐DTP‐NHEtHex ). Both compounds are characterized by low optical bandgaps (1.52 and 1.65 eV, respectively).NBI‐(DTP)2 undergoes oxidative electropolymerization giving the electroactive polymer of ambipolar character. Its two‐step reversible reduction and oxidation is corroborated by complementary EPR and UV/Vis–NIR spectroelectrochemical investigations. The polymer turned out to be electrochemically active not only in aprotic solvents but also in aqueous electrolytes, showing a distinct photocathodic current attributed to proton reduction. Additionally, poly(NBI‐(DTP)2 ) was successfully tested as a photodiode material. Abstract : Two low molecular weight electroactive donor–acceptor–donor (DAD)‐type compounds are reported. Both are characterized by low optical bandgaps. One of these compounds undergoes oxidative electropolymerization giving an electroactive polymer of ambipolar character. The polymer turned out to be electrochemically active not only in aprotic solvents but also in aqueous electrolytes, showing a distinct photocathodic current attributed to proton reduction. The other compound was successfully tested as a photodiode material.